Effect of high concentration of ZnO on the structural and optical properties of silicate glass system - Abed Al-Nidawi, Ali Jabbar; Amin Matori, Khamirul; Mohd Zaid, Mohd Hafiz; Ying Chyi, Josephine Liew; Sin Tee, Tan; Sarmani, Abdul Rahman; Ahmad Khushaini, Muhammad Asif; Md Zain, Ahmad Rifqi; Rahi Mutlage, Wurood (Elsevier, 2024)
An investigation was conducted to explore the optimum composition to fabricate a zinc silicate glass substrate for optoelectronic device applications. The composition was determined based on the empirical formula (ZnO)x-(SiO2)1-x, where x = 0.40, 0.50, 0.60 and 0.70 wt, which was prepared by the conventional melt quenching technique. The focus is on characterizing the physical and structural aspects as well as the optical properties of the glass substrate. The physical properties of zinc silicate samples were assessed using the densitometer and their physical appearance. In addition, the materials' amorphous and glassy characteristics were verified using X-ray diffraction (XRD) and Fourier transform infrared (FTIR) techniques. Finally, ultraviolet–visible (UV–Vis) spectroscopy and photoluminescence spectrometer were used to study the optical properties of samples. The density of the samples was observed to increase from 2805 to 3878 kg/m3 as the percentage of ZnO in the glass composition increased. X-ray diffraction analysis indicated the absence of sharp peaks in the samples containing up to 0.60 wt of ZnO, suggesting the presence of an amorphous phase. Furthermore, the results of this study indicate that ZnO-SiO2 glass substrate samples favor direct forbidden transitions, with an increase in ZnO leading to higher absorption and consequently a lower band gap. The photoluminescence spectrum showed blue light emissions at 422 nm, associating with the variation of band gaps in the ZnO phase. Overall, from the interesting results achieved, this zinc silicate-based composite material at 0.60 wt ZnO can be a potent candidate in optoelectronic applications, among other concentrations used in this study.